Kompleksitas Naratif dari Time Loop dan Perjalanan Waktu dalam Film Indonesia SORE: Istri dari Masa Depan" - Yohanes Yogaprayuda; I Wayan Swandi; Anak Agung Gede Rai Remawa; Gede Pasek Putra Adnyana Yasa (Kartala Virtual Studies, 2026)
This study analyzes the narrative structure of the SORE: Wife from the Future with a focus on the time loop pattern and its integration with time travel elements. The main objective of this study is to examine how the temporal configuration in this film works and to identify possible extensions to the time loop typology formulated by Brütsch. This study uses a descriptive qualitative approach with narrative and interpretive analysis methods of the scenes, dialogues, and time repetition structure in the film. The results show that SORE: Wife from the Future does not fully fit into the four existing variants of the time loop typology, but rather combines the characteristics of several variants simultaneously. This film introduces a hybrid form that combines an external mission (preventing death) and internal transformation (inner healing), as well as uniting time travel and time loops in a cohesive structure. These findings encourage the formulation of a fifth variant in the time loop typology and demonstrate the relevance of the hypertime approach in explaining the logic of transitions between timelines. Keywords: time loop, time travel, temporal structure, SORE: Wife from the Future film